NEGOCIOS Y POLÍTICA EN AMÉRICA LATINA: EL RIESGO POLÍTICO COMO FACTOR IMPONDERABLE PARA LOS INVERSIONISTAS - Nostti, Raúl Bringas (European Scientific Journal, ESJ, 2013)
﻿﻿In recent years, international business analysts and rating agencies have developed a wide array of strategies in order to measure investment risks in different countries. Under the concept of “Country Risk”, pundits believe they are able to foresee the possible problems investors will face when entering a specific market. The imperfect econometric particularities of “Country Risk” analysis have given life to “Political Risk” studies, which pretend, with a sociopolitical stance, to solve the inherent problems of more technical approaches. However, in the case of Latin-American economies, both strategies are of little help, no matter what assurances analysts and rating agencies offer to the public. Latin-American countries are unpredictable. In just a few months, even the best ranked country may become, by unforeseeable circumstances, the ruin of investors. Due to its particular characteristics, Latin-America is prone to major changes in any direction. A strong populist discourse has broad sympathies among the population. Thanks to relatively robust democratic institutions, a change in economic direction is around the corner in every single Latin-American scenario, without the need of a revolution. In this region of the world, “Country Risk” and “Political Risk” analysis are just a rhetorical illusion.